2011
DOI: 10.1111/j.1600-0404.2011.01525.x
|View full text |Cite
|
Sign up to set email alerts
|

Galantamine and behavior in Alzheimer disease: analysis of four trials

Abstract: Galantamine reduces behavioral symptoms in patients with mild to moderate AD, leading to reduced caregiver burden. The reductions were greatest in patients with moderate or advanced moderate disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…According to an analysis of four trials on galantamine and behavior in AD, 5-6 months of galantamine treatment reduced behavioral symptoms of AD and the associated caregiver burden; the beneficial effects on the NPI were reported for galantamine versus a placebo [9,19,20,21]. Moreover, several clinical trials involving galantamine in patients with mild to moderate AD showed improvement of neuropsychiatric symptoms and the associated caregiver distress [19,22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to an analysis of four trials on galantamine and behavior in AD, 5-6 months of galantamine treatment reduced behavioral symptoms of AD and the associated caregiver burden; the beneficial effects on the NPI were reported for galantamine versus a placebo [9,19,20,21]. Moreover, several clinical trials involving galantamine in patients with mild to moderate AD showed improvement of neuropsychiatric symptoms and the associated caregiver distress [19,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Galantamine has allosteric modulating activity at the nicotinic acetylcholine receptors (nAChRs) in addition to acting as an acetylcholinesterase inhibitor (AChEI) [8], and shows improvement of behavioral and neuropsychiatric symptoms [9]. In this study, the efficacy of galantamine on the symptoms of cognition and BPSD was evaluated by an uninterrupted switch from donepezil to galantamine with no washout period or dose titration in amnestic mild cognitive impairment (MCI) and AD patients, whose BPSD were unresponsive to donepezil, or whose caregivers were not satisfied with donepezil treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Compound 2 with the heptyl substituent is one of the most active derivatives. From the group of compounds with two 1,3,4-thiadiazole rings (5,6,7) compound 7 with benzene as a link shows the highest affinity for AChE. Derivative 9 with the 2,4-dichlorophenoxymethyl substituent is the most active against AChE of all compounds of 1,3,4-thiadiazole series.…”
Section: -Chloromentioning
confidence: 99%
“…A common method for the treatment of cognitive and behavioral symptoms of AD is the use of structurally diverse group of cholinesterase inhibitors (ChEIs) with an amine moiety and distinct modes of action. Available ChEI drugs are tacrine (Cognex 3 ), donepezil (Aricept 4 ) galanthamine (Reminyl) -reversible inhibitors 5 and rivastigmine (Exelon 6 ) which acts as a pseudo-irreversible ChEI, and differs in selectivity toward AChE and butyrylcholinesterase (BuChE).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] One of the oldest AD hypotheses, 7) the cholinergic hypothesis, has led to the development of acetylcholinesterase inhibitors (AChEIs) that increase levels of acetylcholine (ACh) through inhibition of acetylcholinesterase (AChE). 8) Several antiacetylcholinesterase agents such as donepezil, 9) tacrine, 10) galantamine, 11) and ensaculin 12) have shown to induce modest improvement in memory and cognitive functions. Unfortunately, the potential effectiveness offered by these inhibitors is often limited by the appearance of central and peripheral side effects.…”
mentioning
confidence: 99%